The development of a linked modelling framework for analysing the socioeconomic impacts of energy and climate policies in South Africa - Merven, Bruno; Arndt, Channing; Winkler, Harald (United Nations University, 2017)
This paper presents some methodological improvements made to the linked SATIM–eSAGE energy-economy-environment modelling framework for analysing energy and climate policy in South Africa. The improvements include the linking of the households and the other economic sectors of the eSAGE economy-wide model to the SATIM energy model. Two scenarios are used to illustrate the benefits of having the new links, which include an energy efficiency scenario and an ambitious climate mitigation scenario. The results show that there are significant socio-economic benefits in having a more energy-efficient economy. The work presented in the paper provides some solid foundations for further work on the energy-economy-environment policy arena for South Africa.